DIRECTIONS OF MANAGING THE USE OF NATURAL RESOURCES IN THE ECONOMY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The management of natural resources in the economy involves implementing strategies and frameworks to ensure that resources are used efficiently, sustainably, and equitably. Below are key directions for managing natural resources: sustainable resource management, resource efficiency and circular economy, integrated resource planning, green technologies and innovation, economic valuation of ecosystem services, regulation and policy frameworks, education and awareness, climate change mitigation and adaptation. By integrating these directions, the economy can transition toward a more sustainable and resilient future, balancing economic growth with the responsible use of natural resources.